Accounting for transparency: A~framework and three applications in tax, managerial, and financial accounting - Jannis Bischof; Joachim Gassen; Anna Rohlfing-Bastian; Davud Rostam-Afschar; Caren Sureth (Schmalenbach Journal of Business Research (SBUR), 2024)
This article presents how the Collaborative Research Center TRR 266 Accounting for Transparency understands and studies transparency in organizations and markets. Starting from our transparency definition, which is rooted in a~sender/receiver framework, we discuss how accounting, taxation, and their regulation affect transparency and illustrate selected economic consequences of transparency. We use three analyses to exemplify our research approach. These analyses illustrate that (i)~firms use tax literacy and tax advice as substitutes in their strategies to cope with signals sent by tax regulators about complex tax regulations, (ii)~trade-offs between tighter management controls and employee motivation lead firms to design hybrid work environments that facilitate information exchange within the firm, and (iii)~managers' understanding of how financial statement users benefit from firm disclosures affects the managers' assessments of disclosure regulation. Overall we argue that transparency is context-specific, hard to achieve, and often has ambiguous consequences. We conclude by highlighting selected transparency-related questions that interdisciplinary work with a~particular emphasis on institutional details can meaningfully address.
Keywords: M41; D82; H25; H32; L21; M12; J24; 650; Business taxation; Disclosure; Financial accounting; Hybrid work; Management controls; Managerial accounting; Tax advice; Tax complexity; Tax literacy; Transparency